Kingdom of the Netherlands-Aruba : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix for the Kingdom of the Netherlands-Aruba underlies long-term growth and fiscal sustainability. Aruba's fiscal position has been deteriorating since the turn of the century, and the medium-term fiscal sustainability analysis shows a continuous weakening ahead of population aging. An upfront and ambitious fiscal consolidation, significantly lowering the deficit and reducing the level of public debt, seems necessary. On the pension front, measures could include increasing the mandatory retirement age and expanding the contribution base.